Comparative study: bench-scale surfactin production from bacillus subtilis using analytical grade and concentrated glycerol from the biodiesel industry - José de Andrade, Cristiano; Paula Resende Simiqueli, Ana; Maria de Andrade, Lidiane; Maria Mendes, Anita; Jauregi, Paula; Maria Pastore, Glaúcia (International Journal of Scientific World, 2016)
The market price of glycerol worldwide tends to decrease, since it is a by-product of biodiesel production. Thus its biotechnological use might lead to significant reduction in the cost of fermentations. The aim of this study was to compare the production of surfactin in peptone culture media supplemented with analytical grade glycerol (AGG) and concentrated glycerol from biodiesel production (CGBP). Differences were observed between the two processes including cell growth and dissolved oxygen consumption. Surfactin yield was 325.19 mg/L with AGG and 71.13 mg/L with CGBP, which proves the impact and importance of the purity of glycerol on the yield of surfactin. In addition, five surfactin homologous were identified by ESI-Q-TOFMS, which were composed by two amino acid sequences ELLMDLD and ELLLDLL. Therefore, as surfactin is a high value-added product, the use of glycerol with high purity is fundamental to achieve higher productivity.